EFFECT OF REPLACEMENT OF SOYBEAN MEAL WITH RICE GLUTEN MEAL ON in vitro FERMENTATION CHARACTERISTICS OF TOTAL MIXED RATION (Applied Biological Research, 2023)
An in vitro study was conducted to assess the effect of using rice gluten  meal as a substitute of soybean meal (SBM) in ruminant diet. The SBM  comprising 12.5% whole diet [total mixed ration (TMR)] was substituted  by rice gluten meal (RGM) on w/w basis at 0, 25, 50, 75 and 100% level.  In vitro dry matter disappearance (IVDMD), organic matter  disappearanc(IVOMD), net gas production, methane production and fermentation efficienof TMRs was assessed. The chemical composition  of TMRs revealed decrease in total ash, acid detergent fiber and total  carbohydrate contents and increase in organic matter, crude protein,  ether extract, neutral detergent fiber, acid detergent lignin, hemicellulose,  neutral detergent insoluble crude protein and acid detergent insoluble  crude protein contents with increase in RGM in TMRs. No significant  difference in net gas production, IVDMD and IVOMD was observed  between the TMR treatments having graded levels of RGM and control.  The NH3-N in TMRs declined with increase in RGM and was highest  (P
Keywords: In vitro digestibilitY; methane; rice gluten meal; ruminants; soybean meal; total mixed ration